2012
DOI: 10.1002/arch.21014
|View full text |Cite
|
Sign up to set email alerts
|

ANNOTATION AND EVOLUTION OF THE ANTIOXIDANT GENES IN THE SILKWORM, Bombyx mori

Abstract: Antioxidant system, which is composed of multiple gene families, plays a major role in reducing oxidative damage and xenobiotic detoxification in all living organisms. We identified 50 silkworm antioxidant genes from nine gene families based on the assembled genome sequence. A comparative analysis of the antioxidant genes of the silkworm with other order insects Anopheles gambiae, Apis mellifera, Drosophila melanogaster, and Tribolium castaneum, was performed. We found that most of the antioxidant gene familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…However, we observed its ortholog in Drosophila (Figure 3). In addition, the anophelines heme peroxidases also experienced a lineage-specific expansion as reported in other insects [33]. The phylogenetic relationship among 16 A. gambiae heme peroxidases and 8 non heme peroxidases revealed that both types of peroxidases appear in two different clades and have diverged from each other a long before ( Figure S3).…”
Section: Hpx15 Is a Unique Anopheline-specific Heme Peroxidasesupporting
confidence: 52%
See 4 more Smart Citations
“…However, we observed its ortholog in Drosophila (Figure 3). In addition, the anophelines heme peroxidases also experienced a lineage-specific expansion as reported in other insects [33]. The phylogenetic relationship among 16 A. gambiae heme peroxidases and 8 non heme peroxidases revealed that both types of peroxidases appear in two different clades and have diverged from each other a long before ( Figure S3).…”
Section: Hpx15 Is a Unique Anopheline-specific Heme Peroxidasesupporting
confidence: 52%
“…This indicates that in A. gambiae there is a large expansion of heme peroxidases and that may be associated with their geographical distribution or biological behaviors as reported in other organisms [33]. It is also noticeable that some lineage-specific heme peroxidses are present only in anophelines and do not have any ortholog in other animals including Aedes and Culex mosquitoes.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations